Access to land and food security. The perspectives of the rural stakeholders of Huambo, Africa - Pepeka, M.E.; Ferreiro, M. F.; Dentinho, T. P. (Revista Portuguesa de Estudos Regionais, 2022)
This paper tries to understand whether access to land in the Central Plateau of Angola can reduce hunger, poverty, food insecurity and thereby contribute to sustainable regional development. The Q Method approach based on the selection and ranking of phrases collected from local authorities allow the identification of different attitudes that constraint sustainable development related to access to land and food security. The State disagrees with the potential of small farms, Family Farms do not agree with the importance of access to land and those who have access to land disagree with the role of the market. Summing up the results of this exercise recognize that access to land is a solution to the hunger and food insecurity that is at odds with governments and the community.